Alternative radiopacifiers for polymethyl methacrylate bone cements: Silane-treated anatase titanium dioxide and yttria-stabilised zirconium dioxide. (May 2021) - Ayre, Wayne Nishio; Scully, Nicole; Elford, Carole; Evans, Bronwen AJ; Rowe, Wendy; Rowlands, Jeff; Mitha, Ravi; Malpas, Paul; Manti, Panagiota; Holt, Cathy; Morgan-Jones, Rhidian; Birchall, James C; et al.
Poly (methyl methacrylate) (PMMA) bone cement is widely used for anchoring joint arthroplasties. In cement brands approved for these procedures, micron-sized particles (usually barium sulphate, BaSO4 ) act as the radiopacifier. It has been postulated that these particles act as sites for crack initiation and subsequently cement fatigue. This study investigated whether alternative radiopacifiers, anatase titanium dioxide (TiO2 ) and yttria-stabilised zirconium dioxide (ZrO2 ), could improve the in vitro mechanical, fatigue crack propagation and biological properties of polymethyl methacrylate (PMMA) bone cement and whether their coating with a silane could further enhance cement performance. Cement samples containing 0, 5, 10, 15, 20 and 25%w/w TiO2 or ZrO2 and 10%w/w silane-treated TiO2 or ZrO2 were prepared and characterised in vitro in terms of radiopacity, compressive and bending strength, bending modulus, fatigue crack propagation, hydroxyapatite forming ability and MC3T3-E1 cell attachment and viability. Cement samples with greater than 10%w/w TiO2 and ZrO2 had a similar radiopacity to the control 10%w/w BaSO4 cement and commercial products. The addition of TiO2 and ZrO2 to bone cement reduced the bending strength and fracture toughness and increased fatigue crack propagation due to the formation of agglomerations and voids. Silane treating TiO2 reversed this effect, enhancing the dispersion and adhesion of particles to the PMMA matrix and resulted in improved mechanical properties and fatigue crack propagation resistance. Silane-treated TiO2 cements had increased nucleation of hydroxyapatite and MC3T3-E1 cell attachment in vitro, without significantly compromising cell viability. This research has demonstrated that 10%w/w silane-treated anatase TiO2 is a promising alternative radiopacifier for PMMA bone cement offering additional benefits over conventional BaSO4 radiopacifiers.